(untitled) (Bangladesh Journal of Medical Education, 2022)
Background: From the beginning of pandemic situation people used to buy, hoard and take different types of medication for the hope of prevention of covid 19. This horrible pandemic situation make people more prone to take medication even antibiotic and more dependent on less reliable sources such as social and digital media for medicine-related information which is mostly observed in developing country. So we have conducted a study to detect the pattern of medicine taken by medical students for preventing purpose of Covid 19. Method: This is a cross sectional, multi centered questionnaire study conducted among medical students during the period of July 2021 to December 2021. Results: In total 425 medical students responded to the questionnaire, in which 17.4% students took Ivermectin. 12.5% respondents experienced adverse drug reactions due to Ivermectin. Approximately half of the respondent (52.47%) consumed Vitamin C and 46.35% received zinc for prevention of COVID 19. 15.52% respondents received Vitamin B and 16.70% received Combination of Vitamin B and zinc. 34.11% respondents took Vitamin D3, among them most of them (49.65%) took 20,000IU. Calcium and combination of Calcium plus Vitamin D also consumed by the respondent (36%) for the preventive goal. Antibiotic also consumed by the respondent (18.1%) for the preventive ground. Conclusion: The study revealed that more or less many respondents took different medicine and supplements for the purpose of survival from COVID -19. Different types of supplements, Ivermectin, and even antibiotic were consumed before vaccine have arrived and those could cause deleterious health effects, unknown drug-drug interaction by their irrational use. Bangladesh Journal of Medical Education Vol.13(2) July 2022: 42-51